Diarrheal Deaths After the Introduction of Rotavirus Vaccination in 4 Countries - Garcia-Calvaro, C (AMER ACAD PEDIATRICS, 2021)
BACKGROUND: We aim in our analysis to estimate the reduction of diarrhea-related mortality rates after introduction of a rotavirus vaccine in subregions of 4 Latin American countries. METHODS: We selected diarrhea-related deaths from individual-level data from death certificates in Brazil, Colombia, Ecuador, and Mexico. Counts were aggregated by region, year and month, and age group for each country. We ran an interrupted time-series analysis using Poisson regression to obtain seasonal and trend-adjusted estimates of impact. Results are reported as percentages (1 - mortality rate ratio). RESULTS: We found a reduction in diarrhea-related mortality in children <5 years old of 18% (95% confidence interval [CI], 15 to 20) for Mexico, 39% (95% CI, 35 to 44) for Colombia, 19 (95% CI, 17 to 22) for Brazil, and -26% (95% CI, -40 to -14) for Ecuador. Using wavelet analyses, we found a reduction of 6- and 12-month seasonality in Brazil, Colombia, and Mexico. We also found that the increased reduction of diarrhea-related deaths was larger with greater prevaccine burden of diarrhea in infants. CONCLUSIONS: Our findings and available evidence support the recommendation from the World Health Organization for the monovalent and/or pentavalent rotavirus vaccine in countries worldwide. We found an increased benefit in those settings with a higher burden of infant diarrhea-related deaths.